The Washback of Intensive TOEFL Training Program (ITTP) on Student’s Learning Motivation - Ahmed Sardi; Zulkifli Surahmat; Sahril Nur (Hasanuddin University, 2022)
This study attempts to quantify the washback effect of the intense TOEFL training program in order to inspire students' learning through improved test scores. The TOEFL results can then be used for academics objectives and faculty requirements. The study was experimental and included a paired-sample t-test and qualitative descriptive design through interviews (a mixed method). Forty (40) students were chosen from any of the departments at IAIN Parepare to participate, and this was done through pretest, treatments, and posttest. The pre-test and post-test employed in the research procedure were both used to determine the students' beginning scores as well as their final scores. The paired-sample t-test in SPSS is then used to assess the data gathered from the pre-test and post-test. The participants are questioned based on the program's experiences in order to acquire information about the students' learning motivation. The outcome revealed that there were sizable variations between the pre-test and post-test scores of the students. It was evident that participants' total TOEFL scores had improved as a result of the intense training. Also, the data from interview illustrated that the students were well-motivated during the training program. This program can enable the participants to have good self-study, nice self-learning preparation, and more desirably confident to learn English or TOEFL.